Effect of structural support size and position on depressed tibial plateau fractures: A finite element analysis - Xiaomeng Ren; Cheng Xu; Yu Jiang; Da Teng; Xinmo Liu; Junsong Wang; Wei Zhang (Heliyon, 2024)
Objective: Structural support for depressed tibial plateau fractures is receiving increasing attention. Currently, there has been little biomechanical evaluation of structural support. This work aimed to investigate the effect of structural support size and position on fracture fixation stability. Methods: A split-depressed tibial plateau fracture model was created according to the fracture map. Cortical screws combined with structural filler were used for fracture fixation. The filler diameter was set to small, medium and large, and the filler position was set to the center and offset by 1, 2 and 3 mm to study the effect of position and size on stability. Results: The maximum stress on the implant in all scenarios occurs at the lower contact surface between the anterior screw and the filler. Increased support size resulted in increased mean maximum screw stress, depressed fragment axial displacement and separated fragment transverse displacement (screw stress: 266.6 ± 37.7 MPa vs. 266.7 ± 51.0 MPa vs. 273.8 ± 41.5 MPa; depressed displacement: 0.123 ± 0.036 mm vs. 0.133 ± 0.049 mm vs. 0.158 ± 0.050 mm; separated displacement: 0.402 ± 0.031 mm VS 0.412 ± 0.047 mm VS 0.437 ± 0.049 mm). The larger the offset of the support position was, the larger the peak screw stress and the larger the reduction loss of depressed and separated fragment reduction, regardless of the support size. The medium support combined with the central position presented the minimum of peak stress and reduction loss. Cortical bone was below 2 % and trabecular strain was below 10 % for all scenarios. Conclusion: Central placement of structural support provides superior stability for the treatment of depressed tibial plateau fractures compared to the eccentric placement. When a support is placed centrally, optimal stability is achieved when the diameter matches the diameter of the depressed region. Thus, the utilization of equal-diameter fillers to provide central support appears to be an ideal selection for depressed tibial plateau fractures.